The Portrayals of Killer Mothers as Folk Devils in Indonesian Online News 2017-2022 - Ruth Adriani Tandio; Jenny Mochtar (Institute of Research and Community Outreach - Petra Christian University, 2022)
This study analyze the portrayal of the mothers who kill the children as folk devil. The theory of folk devil by Stanley Cohen and Erving Goffman’s theories on framing are used to determine the deviant images of the mothers that are created by the news using various means of framing. The mothers who kill the children in the news were depicted as having inhuman characters, having psychological problems, and having a weak nature for dealing with external problems, thus, they are portrayed as folk devils. This portrayal is based on the use of various kinds of elements of construction, such as choice of words, contradiction, perspective, comparison, symbolism, stereotype, exaggeration, highlighted and unhighlighted parts in the news, and assumption as means to frame the killer mother as folk devils. News can be fictionalized for certain purposes. There are many articles used to define mothers as having the quality of deviant characters. Therefore, many news stories in Indonesia are still subjective and biased toward women.